2011
DOI: 10.1073/pnas.1110900108
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of a unique CD57+NKG2Chinatural killer cell subset during acute human cytomegalovirus infection

Abstract: During human CMV infection, there is a preferential expansion of natural killer (NK) cells expressing the activating CD94-NKG2C receptor complex, implicating this receptor in the recognition of CMV-infected cells. We hypothesized that NK cells expanded in response to pathogens will be marked by expression of CD57, a carbohydrate antigen expressed on highly mature cells within the CD56

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

63
718
8
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 684 publications
(813 citation statements)
references
References 64 publications
63
718
8
4
Order By: Relevance
“…As confirmed in this study, the increased number of CD8 + T cells in subjects with CD4/CD8<1 represents an accumulation of highly differentiated memory T cells, and others have shown these cells to be specific for CMV (Hadrup et al 2006;Olsson et al 2000). In parallel, acute and latent CMV infection is associated with the expansion of NK cells with a distinct phenotype (CD57 + NKG2C+; Foley et al 2012;Guma et al 2006a;Lopez-Verges et al 2011;Beziat et al 2013). We recently reported that such NK cell responses to CMV infection lead to stable imprints in the KIR repertoire driven by a clonal-like expansion of NK cells expressing either NKG2C or activating KIRs (Beziat et al 2013).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…As confirmed in this study, the increased number of CD8 + T cells in subjects with CD4/CD8<1 represents an accumulation of highly differentiated memory T cells, and others have shown these cells to be specific for CMV (Hadrup et al 2006;Olsson et al 2000). In parallel, acute and latent CMV infection is associated with the expansion of NK cells with a distinct phenotype (CD57 + NKG2C+; Foley et al 2012;Guma et al 2006a;Lopez-Verges et al 2011;Beziat et al 2013). We recently reported that such NK cell responses to CMV infection lead to stable imprints in the KIR repertoire driven by a clonal-like expansion of NK cells expressing either NKG2C or activating KIRs (Beziat et al 2013).…”
Section: Discussionsupporting
confidence: 76%
“…We also assessed the frequency of ILT-2 + and CD57 + NK cells, which both have been demonstrated to have an increasing frequency on NK cells throughout life (Le Garff-Tavernier et al 2010). ILT-2 binds the CMVencoded UL18 protein and is together with CD57 upregulated on terminally differentiated T and NK cells following acute CMV infection (Northfield et al 2005;Lopez-Verges et al 2011). …”
Section: Flow Cytometrymentioning
confidence: 99%
See 1 more Smart Citation
“…This data also suggests cytokine signaling, in addition to CMV infection, can lead to expansion of NK cells expressing the adaptive marker NKG2C 22, 23, 24. This transition may be supported by changes at a transcription factor level, for example IL‐15 and TGFβ have recently been shown to induce transition of Eomes low to Eomes high NK cells 29.…”
Section: Discussionmentioning
confidence: 77%
“…L'expression de NKG2C est caractéristique d'une population de cellules NK, très augmentée chez les patients humains séro-positifs pour le cytomégalovirus humain (HCMV) [5,6]. Ces cellules NK NKG2C + , qui co-expriment souvent CD57 (un marqueur des cellules NK cytotoxiques), sont maintenues à long terme chez les patients ayant déjà été infectés par HCMV et prolifèrent lors d'une réinfection ou d'une co-infection par d'autres virus.…”
Section: Resultsunclassified